Real-Time Reconciliation Systems: Transforming Transaction Verification in Global Payment Networks - Jayaseelan Shanmugam (International Journal of Computational and Experimental Science and Engineering, 2025)
Traditional reconciliation processes in global payment systems rely on end-of-day batch processing, creating significant delays between transaction execution and verification. Real-time reconciliation represents a paradigm shift that enables instantaneous verification of payment events as they occur, dramatically reducing the time gap between transaction processing and error detection. Event streaming platforms serve as the technological foundation for these systems, capturing and processing payment data including transaction identifiers, amounts, timestamps, and counterparty information in real-time. Reconciliation engines continuously compare incoming payment events against settlement files, authorization logs, and clearing records, enabling immediate identification of discrepancies such as missing payments, duplicate transactions, or settlement failures. Data lineage tracking provides comprehensive visibility into the complete lifecycle of each payment event, facilitating rapid troubleshooting and enhancing financial reporting accuracy. Global remittance companies and cross-border payment providers have successfully implemented these systems to verify fund delivery instantly, with automated alerts flagging discrepancies for immediate investigation. The implementation of real-time reconciliation eliminates traditional delays inherent in batch processing, reduces operational risk, and significantly improves the accuracy and reliability of financial transactions in modern payment ecosystems.